Electrorheological fluid–assisted ultrasonic polishing for IN625 additively manufactured surfaces - Wang, Jingsi; Liu, Xiaohan; Teng, Dezhi; Liew, Pay Jun; Huang, Chaoming (Springer, 2022)
Additive manufacturing (AM) technology develops rapidly and is widely used in various fields. However, high surface roughness of metal components produced by representative AM processes for metallic materials such as laser-based powder bed fusion (L-PBF) is an important problem that needs to be solved. In this work, electrorheological (ER) fluid–assisted ultrasonic polishing is proposed to improve surface finish of metal AM parts. The principle of how an ER fluid works on the polishing process is discussed by calculating the electric field distribution and forces exerted on the abrasive particles. The effects of different field intensities caused by different voltages and electrode gaps on the ultrasonic polishing of AM surfaces are discussed by both experiments and simulations. The motion behaviors of abrasive particles after applying ER fluid are also studied by experimental observations. According to the simulation and experimental results, increasing voltage and reducing electrode gap can improve the electric field intensity, which improves the ER effect and makes a more stable aggregation of abrasive particles in the machining zone. Average surface roughness Ra is reduced to 2.74 μm from the initial value of 5.6 μm after 20 min ER fluid–assisted ultrasonic polishing under the voltage of 2000 V and the electrode gap of 3 mm. Ra improvement of the surface polished with ER effect is 11% higher than that without ER effect. The results show that in a certain range, ER effect can improve the ultrasonic polishing capability and a better surface finish can be obtained.